The Role of Propaganda in Modern Society - Rizokulovich , Rustamov Ramz (Jurnal Humaniora dan Ilmu Pendidikan, 2024)
Purpose: This study aimed to examine the historical development, theoretical foundation, and modern application of the propaganda system as a key mechanism for shaping public opinion, guiding social development, and ensuring societal cohesion in the 21st century. Methodology: This research employs a qualitative approach through literature-based analysis. Key theoretical perspectives from prominent scholars such as Harold Lasswell, Walter Lippmann, and John Dewey are reviewed to understand the evolution of propaganda theories and their relevance to modern societal dynamics. Results: The findings show that the propaganda system has evolved from a basic tool of communication into a complex and structured mechanism for managing public opinion. In modern society, propaganda plays a crucial role in influencing the public’s perception of sociopolitical reforms, promoting shared values, addressing social problems, and mobilizing collective action. Institutions across the political, economic, and cultural sectors actively rely on propaganda to secure support and foster public engagement. Conclusions: The study concludes that propaganda, when used responsibly, functions as a powerful force for social unity, value dissemination, and problem-solving. As societies face ongoing challenges, such as crises and conflicts, the significance of propaganda in shaping collective consciousness and guiding public behavior remains indispensable. Limitations: This study is limited to theoretical and literature-based discourse without empirical data or case studies to support claims. It does not assess the ethical dilemmas or manipulative potential of propaganda in authoritarian contexts. Contributions: This study contributes to the theoretical understanding of propaganda’s societal functions by connecting classical theories with modern implementations. This highlights how propaganda, when aligned with democratic and humanistic values, can be an effective tool for social development, cohesion, and reform.